In situ X-ray imaging and quantitative analysis of balling during laser powder bed fusion of 316L at high layer thickness - Ziao Yan; Shicheng Liu; Zhanpeng Sun; Kangshuo Li; Nan Su; Guang Yang (Materials & Design)
Balling is the main surface defect in additive manufacturing, leading to surface roughness and uneven powder deposition. Through the in-situ X-ray imaging technology, the melting process of high layer thickness 316L powder under different process parameters was investigated in real time in this work. We systematically elaborate the complex formation mechanism of balling at high layer thickness, and the key mechanism underlies the splatter’s coalescence during the flight and solidification stages. The frequent spatters coalescence dominates the large-size balling. The spatter coalescence event was roughly quantified, and the coalescence rate ranges from 42.42 % to 73.04 %. The swing of the irregular balls and jumping of the regular small balls were observed, and the solidification time ranges from 10 ms to 20 ms. Moreover, the detailed morphological parameters including the contact angle and counts of the spatter were clarified, and the algebraic equations about the contact angle and the volumetric energy density were established. This study provides a systematical understanding of the balling phenomenon during laser powder bed fusion of 316L at high layer thickness.